Assessment of the knowledge of dentists about halitosis at two dental teaching hospitals in Khartoum city - KHALIL, Islam; HASSAN , Khadiga (International Arab Journal of Dentistry (IAJD), 2015)
The present study is a descriptive cross-sectional study that was conducted to assess the level of knowledge about halitosis among dental surgeons in Khartoum city. One hundred and six dental surgeons were randomly selected from two dental teaching hospitals: Khartoum Dental Teaching Hospital and Ribat Teaching Hospital in Khartoum city. A fully structured, close ended questionnaire was used. Data collected was assembled and analyzed using the SPSS statistical software. Most of the respondents were general practitioners. The knowledge about the causes and diagnosis of halitosis was generally poor (81%). The awareness about the treatment was generally moderate (37%) and good (38%). No association was found between gender and the level of knowledge about halitosis (p>0.05).A significant association was noted between the level of qualification or the years of clinical experience and the knowledge about the causes and diagnosis of halitosis (p<0.05). The study revealed that dentists lack adequate knowledge regarding causes and diagnosis of halitosis especially for those with lesser years of clinical experience. An increase in knowledge levels could be achieved by emphasizing on this subject during professional training.